2017
DOI: 10.1016/j.neuroscience.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of corticotropin-releasing factor receptor 1 in the developing mouse forebrain: A novel sex difference revealed in the rostral periventricular hypothalamus

Abstract: Corticotropin-releasing factor (CRF) signaling through CRF receptor 1 (CRFR1) regulates autonomic, endocrine and behavioral responses to stress and has been implicated in the pathophysiology of several disorders including anxiety, depression, and addiction. Using a validated CRFR1 reporter mouse line (bacterial artificial chromosome identified by green fluorescence protein (BAC GFP-CRFR1)), we investigated the distribution of CRFR1 in the developing mouse forebrain. Distribution of CRFR1 was investigated at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 82 publications
4
10
0
1
Order By: Relevance
“…A two-way ANOVA revealed a significant sex difference in AVPV/ PeN CRFR1 cells (F(1,26) = 75.50, p ≤ 0.001) matching our previous The current study characterized a novel cluster of CRFR1-ir cells that previous work from our laboratory has shown to be sexually dimorphic from P0-P21 mice (Rosinger et al, 2017). Other AVPV/PeN cell phenotypes such as TH and KISS are known to be more abundant in female than male rodents (Poling & Kauffman, 2013;Scott et al, 2015;Semaan et al, 2010).…”
Section: Adult (P60) Gonadectomy (Gdx) On Crfr1 Expression In the Asupporting
confidence: 89%
See 2 more Smart Citations
“…A two-way ANOVA revealed a significant sex difference in AVPV/ PeN CRFR1 cells (F(1,26) = 75.50, p ≤ 0.001) matching our previous The current study characterized a novel cluster of CRFR1-ir cells that previous work from our laboratory has shown to be sexually dimorphic from P0-P21 mice (Rosinger et al, 2017). Other AVPV/PeN cell phenotypes such as TH and KISS are known to be more abundant in female than male rodents (Poling & Kauffman, 2013;Scott et al, 2015;Semaan et al, 2010).…”
Section: Adult (P60) Gonadectomy (Gdx) On Crfr1 Expression In the Asupporting
confidence: 89%
“…Specifically, CRF/CRFR1 signaling has been shown to facilitate dendrite and synapse formation in the developing olfactory bulb (Garcia et al, ). Notably, AVPV/PeN CRFR1 cell number also appears to decrease between P0 and P60 in both sexes, a decline we have previously reported (Rosinger et al, ). This decrease in CRFR1 cell number might reflect ongoing apoptosis in the AVPV during the postnatal period.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In primates and rodents, adult ACC neurons strongly express the CRF receptor CRFR1 ( Millan et al, 1986 ; Potter et al, 1994 ). It should be noted that the CRFR1 expression level changes dynamically along with postnatal development at many rodent brain areas ( Weathington et al, 2014 ; Zachary et al, 2017 ), as found in the ACC in this study ( Figures 4E – G ). Low expression of CRFR1 in the PVN has been confirmed throughout the development in the above studies as well as in our study.…”
Section: Discussionsupporting
confidence: 67%
“…Dysregulation of this system has been strongly linked with the development of affective disorders (Bangasser and Valentino, 2014). In contrast with the MHb which does not express CRF receptor 1 (CRFR1) positive cells in mice, LHb CRF expression increases over the course of development from P4 onward (Rosinger et al, 2017), highlighting an important distinction between the habenular nuclei. Restraint stress in male Sprague-Dawley rats activated CRF positive neurons in the PVN to a similar extent when the stress occurred in the light or dark cycle, as measured by measured by increased expression of the immediate early gene c-Fos.…”
Section: Mdd Stress and Lhb Dysregulationmentioning
confidence: 99%